TRANSFORMASI NILAI BUDAYA DALAM DUNIA OLAHRAGA TRADISIONAL DAN MODERN : TRANSFORMASI NILAI BUDAYA DALAM DUNIA OLAHRAGA TRADISIONAL DAN MODERN - Evi Enejlika Samosir; Dewi Evalina Siregar; Hallimatul Sa'diyah; Nura Yuliati Siregar; Erikson Situmorang; Hamzah Awaludin; Luga Marcelino Sinaga; Alex Pakpahan; Jose Xanana Gusmau Purba; Yan Indra Siregar; Putra Arima (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Sports are social and cultural activities that are not only focused on health and achievement but also embody social values, norms, ethics, and the cultural identity of a community. The development of globalization and modernization has brought about changes in sports practices, particularly in the relationship between traditional and modern sports. This article aims to analyze the transformation of cultural values in the world of traditional and modern sports through a literature review approach. Data were obtained from various academic sources, including books, scientific journals, and relevant documents related to sports, culture, and social change. The results of the study indicate that sports play a significant role in shaping social values such as sportsmanship, cooperation, discipline, and solidarity. Furthermore, sports norms and ethics serve as the foundation for maintaining the integrity and quality of sports practices. Traditional sports function as a medium for preserving culture and community identity, whereas modern sports have evolved with characteristics of professionalism, standardized rules, and a performance-oriented focus. The transition from traditional sports to modern sports has had a positive impact in the form of advancements in sports science and the professionalization of sports; however, it also has the potential to cause a shift in cultural values and a decline in the presence of traditional sports. Therefore, efforts at preservation and adaptation are necessary to ensure that cultural values in sports are maintained amid the development of modern sports.